Epigenetic Markers Are Associated With Differences in Isocyanate Biomarker Levels in Exposed Spray-Painters - Taylor, Laura W.; French, John E.; Robbins, Zachary G.; Nylander-French, Leena A. (Frontiers in Genetics, 2021)
Isocyanates are respiratory and skin sensitizers that are one of the main causes of occupational asthma globally. Genetic and epigenetic markers are associated with isocyanate-induced asthma and, before asthma develops, we have shown that genetic polymorphisms are associated with variation in plasma and urine biomarker levels in exposed workers. Inter-individual epigenetic variance may also have a significant role in the observed biomarker variability following isocyanate exposure. Therefore, we determined the percent methylation for CpG islands from DNA extracted from mononuclear blood cells of 24 male spray-painters exposed to 1,6-hexamethylene diisocyanate (HDI) monomer and HDI isocyanurate. Spray-painters’ personal inhalation and skin exposure to these compounds and the respective biomarker levels of 1,6-diaminohexane (HDA) and trisaminohexyl isocyanurate (TAHI) in their plasma and urine were measured during three repeated industrial hygiene monitoring visits. We controlled for inhalation exposure, skin exposure, age, smoking status, and ethnicity as covariates and performed an epigenome-wide association study (EWAS) using likelihood-ratio statistical modeling. We identified 38 CpG markers associated with differences in isocyanate biomarker levels (Bonferroni <0.05). Annotations for these markers included 17 genes: ALG1, ANKRD11, C16orf89, CHD7, COL27A, FUZ, FZD9, HMGN1, KRT6A, LEPR, MAPK10, MED25, NOSIP, PKD1, SNX19, UNC13A, and UROS. We explored the functions of the genes that have been published in the literature and used GeneMANIA to investigate gene ontologies and predicted protein-interaction networks. The protein functions of the predicted networks include keratinocyte migration, cell-cell adhesions, calcium transport, neurotransmitter release, nitric oxide production, and apoptosis regulation. Many of the protein pathway functions overlap with previous findings on genetic markers associated with variability both in isocyanate biomarker levels and asthma susceptibility, which suggests there are overlapping protein pathways that contribute to both isocyanate toxicokinetics and toxicodynamics. These predicted protein networks can inform future research on the mechanism of allergic airway sensitization by isocyanates and aid in the development of mitigation strategies to better protect worker health.